The decoding schemes of LDPC-codes. The efficiency ratings, advantages and further developments of LDPC-codes - A. G. Soltanov (Безопасность информационных технологий, 2010)
This article concerns the problems of information decoding, using LDPC-code and describes different decoding schemes. It is also described that LDPC codes are selected as the DVB-S2 standard over 7 other turbo code based candidates because of its more efficient implementation as well as better performance. The article deals with the questions of decoding nonbinary LDPC-code and it’s comparison with Reed—Solomon code